Development of Physics Laboratory Assistance to Improve Higher Order Thinking Skills in Simple Harmonic Motion for High School Students - Astriani, Devi; Murdani, Eka; Soeharto, Soeharto (Variabel, 2024)
This study aims to (1) produce Physics Laboratory Assistance (PLA) that is suitable for use, (2) determine the percentage of Higher Order Thinking Skills (HOTS) using PLA, (3) describe students' HOTS using Rasch modelling analysis, (4) determine the effectiveness of students' HOTS on simple harmonic motion materials in learning. This type of research was research and development (R&D) adapted according to the Borg & Gall model. Data collection used interviews, questionnaires, and test methods. The subjects in this research were students of class X IPA1 MA Ushuluddin Singkawang, X IPA1 and X IPA2 SMAN 1 Selakau. The instrument was declared to be valid in terms of content and empirically by following the analysis of Rasch modelling with the help of the Winstep 3.37 program. The results of the content validation showed that PLA was feasible to use with an average score of 3.61 in the excellent category. The percentage of HOTS of students was analyzed using the Microsoft Excel application in the extensive trial of the experimental class and the control class with an average pretest score of 38.90 and posttest of 39.90. The description of the student's HOTS was analyzed using Rasch modelling, it was obtained that the ability to evaluate is the ability that is most mastered by the student, then create and analyze. The effectiveness of HOTS in students was known to use PLA in learning using effect size obtained in a limited trial of 0.14 and a broad trial of 0.15 with a low category.